If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(c + -5) + s(c + -5) = 0 Reorder the terms: a(-5 + c) + s(c + -5) = 0 (-5 * a + c * a) + s(c + -5) = 0 (-5a + ac) + s(c + -5) = 0 Reorder the terms: -5a + ac + s(-5 + c) = 0 -5a + ac + (-5 * s + c * s) = 0 Reorder the terms: -5a + ac + (cs + -5s) = 0 -5a + ac + (cs + -5s) = 0 Solving -5a + ac + cs + -5s = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1cs' to each side of the equation. -5a + ac + cs + -1cs + -5s = 0 + -1cs Combine like terms: cs + -1cs = 0 -5a + ac + 0 + -5s = 0 + -1cs -5a + ac + -5s = 0 + -1cs Remove the zero: -5a + ac + -5s = -1cs Add '5s' to each side of the equation. -5a + ac + -5s + 5s = -1cs + 5s Combine like terms: -5s + 5s = 0 -5a + ac + 0 = -1cs + 5s -5a + ac = -1cs + 5s Reorder the terms: -5a + ac + cs + -5s = -1cs + cs + 5s + -5s Combine like terms: -1cs + cs = 0 -5a + ac + cs + -5s = 0 + 5s + -5s -5a + ac + cs + -5s = 5s + -5s Combine like terms: 5s + -5s = 0 -5a + ac + cs + -5s = 0 The solution to this equation could not be determined.
| g=3g+3u | | 20a^2-23ab+6b^2=0 | | 5(6z-1)-3(z+3)=11(z+1) | | 9x-(4x-5)-(-6x+1)= | | 22=0 | | 11x-77=0 | | 3x^2-25x+42=0 | | 275m^2+396n^2=0 | | 4y+112=180 | | x^2-x-48=16 | | 0.5(x-0.08)=0 | | x/3=3x-1 | | ln(x)+ln(8x)=-3 | | 5y+20=0 | | 5b+7b=60 | | s^2-12s+36= | | (x-2)/3=8 | | (x-2)/3-5=3 | | 4x^3+12x^2+10x+10=0 | | x-2/3-5=3 | | 2x+30+x= | | 24=-8(0.3p+9) | | 4(3x-2)=(6x+6) | | 4X+37+9X=180 | | X=45(16) | | 29x^2-7x=0 | | 0.50x+0.45(90)=0.25(124) | | 5x+8-12=-6x-2x+3 | | -4x-6+x=-2x+6-10 | | 0(n)=2n-1 | | -8(v+4)+2v+6=7v+9 | | (x+7)(x+6)= |